Staff Turnover and Organizational Performance: A Case of Kabale District Local Government - Pross, Tukamuhebwa (Kabale University, 2022)
Research Dissertation Submitted to the Directorate of Postgraduatein Partial Fulfillment of the Requirements for the Award of a Master’s Degree in Public Administration and Management of Kabale University